Green targeting gold adsorbent suitable for trace gold in high-acid multi-element solution and preparation method of green targeting gold adsorbent

By performing sulfonation and hydrothermal reaction in biomass, a green targeted gold adsorbent suitable for trace gold in high acid multivariate solution was prepared, which solved the problem of difficulty in efficient recovery of trace gold in the prior art, and achieved efficient and highly selective gold adsorption effect.

CN119500072APending Publication Date: 2025-02-25JIANGXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411678041.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

It is difficult for the prior art to efficiently recover trace amounts of gold in high acid multivariate solutions, especially below the Au3+ content of 200 mg/L. Techniques such as ion exchange, solvent extraction and reduction replacement are difficult to achieve green and efficient recovery of gold.

Method used

The biomass is added with water and concentrated sulfuric acid for sulfonation, and then mixed with N235 for hydrothermal reaction. After neutralization, washing and drying, a green targeted gold adsorbent suitable for trace amounts of gold in a high acid multi-solution is prepared.

Benefits of technology

Targeted adsorption of trace gold in a highly acid multivariate complex solution is achieved, with an adsorption rate of more than 99.5%, an adsorption rate of impurity elements is less than 10.0%, and the raw materials are green and environmentally friendly, and the preparation process is simple.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500072A_ABST
    Figure CN119500072A_ABST
Patent Text Reader

Abstract

The invention discloses a green targeting gold adsorbent suitable for trace gold in a high-acid multi-element solution and a preparation method of the green targeting gold adsorbent, and belongs to the field of secondary resource recycling, the green targeting gold adsorbent can adsorb 150-250 mg / L of an Au < 3 + > solution to 1 mg / L or below aiming at a trace gold solution in a gold-absorbed solution in the copper smelting process, the adsorption rate reaches 99.5% or above, the adsorption rates of impurity elements As, Bi, Cu, Pb and Te are all lower than 10.0%, and the green targeting gold adsorbent is suitable for the trace gold solution in the gold-absorbed solution in the copper smelting process. Targeted adsorption of trace gold in a high-acid multi-element complex solution system can be achieved. The waste is turned into wealth, the raw materials of the adsorbent are green and environment-friendly, and the preparation process
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary resource recovery, and in particular relates to a green targeted gold adsorbent suitable for trace gold in a high-acid polybasic solution and a preparation method thereof. Background Art

[0002] In 2023, the global gold reserves will be 59,000 tons, and the total demand for gold will be 4,448.4 tons. Gold mainly comes from copper anode mud produced in the copper smelting process. my country's refined copper output is about 12.988 million tons, and copper anode mud is about 103,000 tons. Copper anode mud contains precious metals Au, Ag, Pt, Pd, scattered metals Se, Te, and various base metals such as Pb, As, Sb, Bi, Sn, Cu, etc. At present, the copper anode mud disposal technology is becoming more and more perfect, but it also produces a large amount of high-acid multi-component complex solutions. The technology for extracting and recovering gold from high-concentration gold solutions is relatively mature, but for trace gold solutions, especially 200 mg / L Au 3+ Below the gold content, it is difficult to achieve green and efficient recovery of gold using technologies such as ion exchange, solvent extraction, and reduction substitution.

[0003] Adsorbents are widely used in trace gold solutions. Among them, biomass adsorbent materials have attracted much attention due to their low cost, sustainable renewability, easy modification and preparation, and wide range of raw materials. Compared with ion exchange resins, they have outstanding advantages in cost and environmental friendliness. In recent years, many outstanding research results have emerged in the preparation of biomass adsorbents for gold adsorption, including rice husk (10.1016 / j.hydromet.2024.106304), persimmon residue (10.1016 / j.biortech.2014.03.164), banana peel (10.1016 / j.wasman.2020.05.053), persimmon tannin (10.1016 / j.jhazmat.2020.05.053), and ion exchange resin (10.1016 / j.hydromet.2024.106304). 2018.05.061), garlic peel (10.1007 / s11356-022-19584-2), etc. Its modification and preparation techniques include cross-linking modification (10.1016 / j.msec.2017.05.038), polyethyleneimine modification (10.1016 / j.seppur.2017.12.024) and sulfonation (10.1016 / j.colsurfa.2024.134738), etc. However, due to factors such as small adsorption capacity, unobtrusive selectivity advantage of gold adsorption, cumbersome modification process and high cost, it is often far from industrialization and practical application. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes a green targeted gold adsorbent suitable for trace gold in high-acid polybasic solution and its preparation method. For the trace gold solution in the copper smelting process, the shaking bottle adsorption method can be used to absorb 150-250 mg / L of Au 3+ The solution is adsorbed to less than 1 mg / L, the adsorption rate is more than 99.5%, and the adsorption rates of impurity elements As, Bi, Cu, Pb, and Te are all lower than 10.0%, which can achieve targeted adsorption of trace gold in a high-acid multi-component complex solution system. The invention turns waste into treasure, the raw materials of the adsorbent are green and environmentally friendly, and the preparation process is simple.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A method for preparing a green targeted gold adsorbent suitable for trace gold in a high-acid polybasic solution comprises the following steps:

[0008] (1) adding water and concentrated sulfuric acid to the biomass to perform sulfonation treatment to obtain sulfonated biomass;

[0009] (2) mixing the sulfonated biomass with N235 (n-trioctylamine) to carry out a hydrothermal reaction, and after the reaction is completed, performing solid-liquid separation to obtain a solid product as a hydrothermal synthesis product;

[0010] (3) neutralizing the hydrothermal synthesis product with a sodium hydroxide (NaOH) solution, filtering, washing the filtered solid with an ethanol solution and water, respectively, and centrifuging to obtain a neutralized product;

[0011] (4) Drying the neutralized product under an inert atmosphere, grinding and screening to obtain the green targeted gold adsorbent suitable for trace gold in high-acid polybasic solution.

[0012] The invention proposes a green targeted gold adsorbent suitable for trace gold in a high-acid polybasic solution and a preparation method thereof. The adsorbent is easily available, the preparation process is simple, the adsorption rate for trace gold in the high-acid polybasic solution is fast, the adsorption capacity is high, and the selectivity is strong.

[0013] Preferably, in step (1), the biomass includes corn cobs, wheat straw or corn straw.

[0014] Preferably, in step (1), the mass volume ratio of the biomass, water and concentrated sulfuric acid is 20 g:50 mL:50 mL.

[0015] Preferably, in step (1), the sulfonation process comprises:

[0016] Water and concentrated sulfuric acid are added to the biomass in sequence, and the mixture is stirred continuously. After the biomass is completely carbon black, the biomass is vacuum dried, sealed and allowed to stand for three hours to obtain the sulfonated biomass.

[0017] Preferably, in step (1), the concentration of the concentrated sulfuric acid is 18 mol / L

[0018] Preferably, in step (2), the mass volume ratio of the sulfonated biomass to N235 is (0.5-2) g:1 mL.

[0019] Preferably, in step (3), the step of obtaining the neutralized product is:

[0020] Water was added to the hydrothermal synthesis product, and the pH was adjusted to 7.00 using a NaOH solution, and the product was filtered. The filtered solid was first washed three times with a 40% by volume ethanol solution, and then washed three times with deionized water, and centrifuged to obtain a neutralized product.

[0021] Preferably, the concentration of the NaOH solution is 4 mol / L.

[0022] Preferably, in step (4), the inert atmosphere is argon, the drying temperature is 120° C., the heating rate during the drying process is 7° C. / min, and the argon flow rate is 0.5 L / min.

[0023] More preferably, when the biomass is corn cobs, the preparation method of the green targeted gold adsorbent suitable for trace gold in high-acid polybasic solution is:

[0024] (1) Sulfonation: Weigh 20.0000 g corn cob and add it to a beaker. Then, measure 50 mL of distilled water and add it to the beaker. Measure 50 mL of concentrated sulfuric acid (concentration is 18 mol / L) and slowly add it to the beaker. Stir with a glass rod to ensure that the corn cob is fully in contact with the concentrated sulfuric acid. After the corn cob is completely carbonized, put it into a vacuum dryer with a vacuum degree of 1×10 -1 MPa, sealed and allowed to stand for three hours to obtain sulfonated corncob;

[0025] (2) N235 modification: The sulfonated corncob and 20 mL of N235 were poured into a hydrothermal synthesis reactor, placed in a homogeneous reactor and rotated for three hours at room temperature and pressure to ensure that N235 and the sulfonated corncob were fully in contact. After the reaction, the mixed liquid was separated into solid and liquid, and the obtained solid was the hydrothermal synthesis product;

[0026] (3) Neutralization: 150 mL of deionized water was added to the hydrothermal synthesis product obtained in step (2), and the pH was adjusted to 7.00 using a 4 mol / L NaOH solution, and filtered. The filtered solid was first washed three times with 10 mL of a 40% by volume ethanol solution, and then washed three times with 10 mL of deionized water (i.e., the filtered solid was first washed three times with a 40% by volume ethanol solution, and then washed three times with deionized water), and then solid-liquid separation was performed in a centrifuge to obtain a neutralized product. The rotation speed of the centrifuge was 3000 rpm, and the centrifugation time was 10 min.

[0027] (4) Drying: The neutralized product obtained in step (3) is transferred into a vacuum tube furnace and dried for 12 h by passing argon gas. The temperature of the vacuum tube furnace is set to 120° C., the heating rate is 7° C. / min, and the argon flow rate is 0.5 L / min. The product is ground and passed through a 40-mesh screen to obtain a corncob sulfonated-modified adsorbent, which is a green targeted gold adsorbent suitable for trace gold in high-acid polybasic solutions.

[0028] The second technical solution of the present invention:

[0029] The present invention also provides a green targeted gold adsorbent suitable for adsorbing trace gold in a high-acid polybasic solution, which is prepared according to the method.

[0030] The third technical solution of the present invention:

[0031] The present invention also provides the use of the green targeted gold adsorbent in the targeted adsorption of gold in a high-acid polybasic solution.

[0032] Compared with the prior art, the present invention has the following advantages and technical effects:

[0033] Au in acidic chlorinated solution is AuCl 4 - The complex ion exists, as shown in Formula 1. The present invention uses sulfuric acid to sulfonate biomass, which contains a large amount of cellulose. The surface of cellulose is functionalized by sulfonic acid groups and presents a positive charge under acidic conditions, which is beneficial to the negatively charged AuCl 4 - Electrostatic adsorption of ions. The sulfonic acid group reacts with strong acid to generate [R-SO 3 H 2 ] + , (R represents biomass) as shown in Formula 2, the generated [R-SO 3 H 2 ] + Can be used with AuCl 4 - An anion exchange reaction occurs, as shown in Formula 3. Using N235 modified sulfonated adsorbent, the tertiary amine groups on the surface of the modified adsorbent react with strong acid to form R 3 NH+ , as shown in Formula 4, will react with AuCl 4 - Anion exchange reaction occurs, as shown in Formula 5. However, impurity ions such as As, Bi, Cu, and Pb exist as metal cations or acid radicals and do not react with [R-SO 3 H 2 ] + and R 3 NH + The reaction occurs, thus achieving targeted adsorption of trace amounts of gold from high-acid polybasic solutions.

[0034]

[0035] R-SO 3 H+HCl=R-S0 3 H 2 Cl Formula 2

[0036]

[0037] R 3 N+HCl=R 3 NHCl Formula 4

[0038]

[0039] The adsorbent prepared by the present invention is used for the trace gold solution in the copper smelting process after the gold absorption liquid, and the 150-250 mg / L Au is adsorbed by the shaking bottle adsorption method. 3+ The solution is adsorbed to below 1 mg / L, with an adsorption rate of over 99.5%, and the adsorption rates of impurity elements As, Bi, Cu, Pb, and Te are all lower than 10.0%, which can achieve targeted adsorption of trace gold in high-acid multi-component complex solution systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0041] Figure 1 The present invention is a flow chart for preparing a green targeted gold adsorbent suitable for trace gold in a high-acid polybasic solution;

[0042] Figure 2 The adsorption-desorption curve of the corncob sulfonated-modified adsorbent prepared in Example 1;

[0043] Figure 3 The electron microscope image and energy spectrum of the corncob sulfonated-modified adsorbent after gold adsorption in Example 1, wherein the bright white dots represent gold. DETAILED DESCRIPTION

[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0045] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0049] In the present invention, "normal pressure" refers to 1 atmosphere (101.325 kPa), and "normal temperature" refers to 25±2°C.

[0050] In the present invention, "trace gold" refers to Au in the solution. 3+ The content is below 250mg / L.

[0051] In the present invention, "high acid polybasic solution" refers to the trace gold solution in the solution after gold absorption during copper smelting, wherein "high acid" refers to the C(H + ) is 1.995; “Multi-element” means that in addition to Au, the solution also contains other metal ions (such as As, Bi, Cu, Pb and Te, etc.).

[0052] All raw materials used in the examples of the present invention are commercially available.

[0053] The preparation flow chart of the green targeted gold adsorbent suitable for trace gold in high-acid polybasic solution is shown in Figure 1 .

[0054] The technical solution of the present invention is further illustrated by the following embodiments.

[0055] Example 1

[0056] Preparation method of adsorbent: (1) Sulfonation: Weigh 20.0000 g corn cob and add it to a beaker. Then, measure 50 mL of distilled water and add it to the beaker. Measure 50 mL of concentrated sulfuric acid (concentration is 18 mol / L) and slowly add it to the beaker. Stir with a glass rod to ensure that the corn cob is in full contact with the concentrated sulfuric acid. After the corn cob is completely carbonized, put it into a vacuum dryer with a vacuum degree of 1×10 - 1 MPa, sealed and allowed to stand for three hours to obtain sulfonated corncob;

[0057] (2) N235 modification: 15.6450 g of sulfonated corncob and 20 mL of N235 were poured into a hydrothermal synthesis reactor, placed in a homogeneous reactor and rotated for three hours at room temperature and pressure to ensure that N235 and sulfonated corncob were fully in contact. After the reaction, the mixed liquid was separated into solid and liquid, and the obtained solid was the hydrothermal synthesis product;

[0058] (3) Neutralization: 150 mL of deionized water was added to the hydrothermal synthesis product obtained in step (2), and the pH was adjusted to 7.00 using a 4 mol / L NaOH solution, followed by filtering. The filtered solid was first washed three times with 10 mL of a 40% by volume ethanol solution, and then washed three times with 10 mL of deionized water. The solid was then separated into a solid and a liquid in a centrifuge to obtain a neutralized product. The rotation speed of the centrifuge was 3000 rpm, and the centrifugation time was 10 min.

[0059] (4) Drying: The neutralized product obtained in step (3) was transferred into a vacuum tube furnace and dried for 12 h by passing argon gas. The temperature of the vacuum tube furnace was set to 120° C., the heating rate was 7° C. / min, and the argon flow rate was 0.5 L / min. The product was ground and passed through a 40-mesh screen to obtain 29.5423 g of corn cob sulfonated-modified adsorbent, which is a green targeted gold adsorbent suitable for trace gold in high-acid polybasic solution.

[0060] The adsorption-desorption curve of the corncob sulfonated-modified adsorbent prepared in this example is shown in Figure 2 It can be seen that the adsorption-desorption curve of the modified corncob shows an H3-type hysteresis loop, and it does not show adsorption saturation in the relatively high pressure region, proving that its mesoporous structure is very irregular.

[0061] Take high acid (C(H + )=1.995), 20mL of multi-element trace gold solution, 0.0400g of corncob sulfonated-modified adsorbent, at room temperature, oscillate in a constant temperature oscillator for 24h, with a rotation speed of 250r / min. After analysis and calculation, the adsorbent prepared in this embodiment has an Au adsorption rate of 99.6%, an As adsorption rate of 0.4%, a Bi adsorption rate of 3.5%, a Cu adsorption rate of 6.1%, a Pb adsorption rate of 2.2%, and a Te adsorption rate of 5.3%. The pH value of the solution after adsorption is 1.84 measured by a pH meter. The specific results are shown in Table 1. It can be seen that the adsorbent of the present invention can achieve targeted adsorption of gold.

[0062] Table 1 Example 1 Adsorbent adsorption results

[0063]

[0064] The electron microscope image and energy spectrum of the corncob sulfonated-modified adsorbent after gold adsorption in Example 1 are shown in Figure 3 , where the bright white dots represent gold, indicating that the gold in the solution was adsorbed onto the modified biomass adsorbent.

[0065] Example 2

[0066] Preparation method of adsorbent: (1) Sulfonation: Weigh 20.0000 g wheat straw and add it to a beaker. Then, measure 50 mL of distilled water and add it to the beaker. Measure 50 mL of concentrated sulfuric acid (concentration is 18 mol / L) and slowly add it to the beaker. Stir with a glass rod to ensure that the wheat straw is in full contact with the concentrated sulfuric acid. After the wheat straw is completely carbonized, put it into a vacuum dryer with a vacuum degree of 1×10 -1 MPa, sealed and left to stand for three hours to obtain sulfonated wheat straw;

[0067] (2) N235 modification: 16.5572 g of sulfonated wheat straw and 20 mL of N235 were poured into a hydrothermal synthesis reactor, placed in a homogeneous reactor and rotated for three hours at room temperature and pressure to ensure that N235 and sulfonated wheat straw were fully in contact. After the reaction, the mixed liquid was separated into solid and liquid, and the obtained solid was the hydrothermal synthesis product;

[0068] (3) Neutralization: 150 mL of deionized water was added to the hydrothermal synthesis product obtained in step (2), and the pH was adjusted to 7.00 using a 4 mol / L NaOH solution, followed by filtering. The filtered solid was first washed three times with 10 mL of a 40% by volume ethanol solution, and then washed three times with 10 mL of deionized water. The solid was then separated into a solid and a liquid in a centrifuge to obtain a neutralized product. The rotation speed of the centrifuge was 3000 rpm, and the centrifugation time was 10 min.

[0069] (4) Drying: The neutralized product obtained in step (3) was transferred into a vacuum tube furnace and dried for 12 h by passing argon gas. The temperature of the vacuum tube furnace was set to 120° C., the heating rate was 7° C. / min, and the argon flow rate was 0.5 L / min. The product was ground and passed through a 40-mesh screen to obtain 34.4170 g of wheat straw sulfonated-modified adsorbent, which is a green targeted gold adsorbent suitable for trace gold in high-acid polybasic solution.

[0070] Take high acid (C(H + )=1.995), 20mL of multi-element trace gold solution, 0.0400g of wheat straw sulfonated-modified adsorbent, at room temperature, oscillate in a constant temperature oscillator for 24h, with a rotation speed of 250r / min. After analysis and calculation, the adsorbent prepared in this embodiment has an adsorption rate of 99.6% for Au, 0.5% for As, 6.1% for Bi, 7.0% for Cu, 2.9% for Pb, and 4.6% for Te. The pH value of the solution after adsorption is measured by a pH meter to be 1.86. The specific results are shown in Table 2.

[0071] Table 2 Adsorption results of adsorbents in Example 2

[0072]

[0073] Example 3

[0074] Preparation method of adsorbent: (1) Sulfonation: Weigh 20.0000 g corn stalks and add them to a beaker. Then, measure 50 mL of distilled water and add it to the beaker. Measure 50 mL of concentrated sulfuric acid (concentration is 18 mol / L) and slowly add it to the beaker. Stir with a glass rod to ensure that the corn stalks are in full contact with the concentrated sulfuric acid. After the corn stalks are completely carbonized, place them in a vacuum dryer with a vacuum degree of 1×10 -1 MPa, sealed and allowed to stand for three hours to obtain sulfonated corn stover;

[0075] (2) N235 modification: 17.6430 g of sulfonated corn straw and 20 mL of N235 were poured into a hydrothermal synthesis reactor and placed in a homogeneous reactor and rotated for three hours at room temperature and pressure to ensure that N235 and sulfonated corn straw were fully in contact. After the reaction, the mixed liquid was separated into solid and liquid, and the obtained solid was the hydrothermal synthesis product.

[0076] (3) Neutralization: 150 mL of deionized water was added to the hydrothermal synthesis product obtained in step (2), and the pH was adjusted to 7.00 using a 4 mol / L NaOH solution, followed by filtering. The filtered solid was first washed three times with 10 mL of a 40% by volume ethanol solution, and then washed three times with 10 mL of deionized water. The solid was then separated into a solid and a liquid in a centrifuge to obtain a neutralized product. The rotation speed of the centrifuge was 3000 rpm, and the centrifugation time was 10 min.

[0077] (4) Drying: The neutralized product obtained in step (3) was transferred into a vacuum tube furnace and dried for 12 h by passing argon gas. The temperature of the vacuum tube furnace was set to 120° C., the heating rate was 7° C. / min, and the argon flow rate was 0.5 L / min. The product was ground and passed through a 40-mesh screen to obtain 33.8450 g of corn straw sulfonated-modified adsorbent, which is a green targeted gold adsorbent suitable for trace gold in high-acid polybasic solution.

[0078] Take high acid (C(H + )=1.995), 20mL of multi-element trace gold solution, 0.0400g of corn straw sulfonated-modified adsorbent, at room temperature, oscillate in a constant temperature oscillator for 24h, with a rotation speed of 250r / min. After analysis and calculation, the adsorbent of this embodiment has an adsorption rate of 99.9% for Au, 0.4% for As, 3.5% for Bi, 5.0% for Cu, 6.8% for Pb, and 6.4% for Te. The pH value of the solution after adsorption is measured by a pH meter to be 1.89. The specific results are shown in Table 3.

[0079] Table 3 Adsorption results of adsorbents in Example 3

[0080]

[0081] Comparative Example 1

[0082] Preparation method of adsorbent: (1) Sulfonation: Weigh 20.0000 g corn cob and add it to a beaker. Then, measure 50 mL of distilled water and add it to the beaker. Measure 50 mL of concentrated sulfuric acid (concentration is 18 mol / L) and slowly add it to the beaker. Stir with a glass rod to ensure that the corn cob is in full contact with the concentrated sulfuric acid. After the corn cob is completely carbonized, put it into a vacuum dryer with a vacuum degree of 1×10 - 1 MPa, sealed and allowed to stand for three hours to obtain sulfonated corncob;

[0083] (2) Neutralization: 150 mL of deionized water was added to the sulfonated corncob obtained in step (1), and the pH was adjusted to 7.00 using a 4 mol / L NaOH solution, followed by filtering. The filtered solid was first washed three times with 10 mL of a 40% by volume ethanol solution, and then washed three times with 10 mL of deionized water. The solid was then separated into a solid and a liquid in a centrifuge to obtain a neutralized product. The rotation speed of the centrifuge was 3000 rpm, and the centrifugation time was 10 min.

[0084] (3) Drying: The neutralized product obtained in step (2) was transferred into a vacuum tube furnace and dried for 12 h by passing argon gas. The temperature of the vacuum tube furnace was set to 120° C., the heating rate was 7° C. / min, and the argon flow rate was 0.5 L / min. The product was ground and passed through a 40-mesh screen to obtain 15.6850 g of corncob sulfonated adsorbent.

[0085] Take high acid (C(H + )=1.995), 20mL of multi-element trace gold solution, 0.0400g of corncob sulfonated adsorbent, at room temperature, oscillate in a constant temperature oscillator for 24h, with a rotation speed of 250r / min. After analysis and calculation, the adsorbent prepared in this embodiment has an Au adsorption rate of 39.6%, an As adsorption rate of 0.2%, an Bi adsorption rate of 2.4%, an Cu adsorption rate of 5.6%, an Pb adsorption rate of 1.7%, and an Te adsorption rate of 5.2%. The pH value of the solution after adsorption is measured by a pH meter to be 1.84. The specific results are shown in Table 4.

[0086] Table 4 Comparative Example 1 Adsorbent adsorption results

[0087]

[0088] It can be seen from Table 4 that in Comparative Example 1, N235 modification was not used, and the adsorption rate of Au by the prepared adsorbent was relatively low.

[0089] Comparative Example 2

[0090] Preparation method of adsorbent: (1) Sulfonation: Weigh 20.0000 g wheat straw and add it to a beaker. Then, measure 50 mL of distilled water and add it to the beaker. Measure 50 mL of concentrated sulfuric acid (concentration is 18 mol / L) and slowly add it to the beaker. Stir with a glass rod to ensure that the wheat straw is in full contact with the concentrated sulfuric acid. After the wheat straw is completely carbonized, put it into a vacuum dryer with a vacuum degree of 1×10 -1 MPa, sealed and left to stand for three hours to obtain sulfonated wheat straw;

[0091] (2) Neutralization: 150 mL of deionized water was added to the sulfonated wheat straw obtained in step (1), and the pH was adjusted to 7.00 using a 4 mol / L NaOH solution, followed by filtering. The filtered solid was first washed three times with 10 mL of a 40% by volume ethanol solution, and then washed three times with 10 mL of deionized water. The solid was then separated into a solid and a liquid in a centrifuge to obtain a neutralized product. The rotation speed of the centrifuge was 3000 rpm, and the centrifugation time was 10 min.

[0092] (3) Drying: The neutralized product obtained in step (2) was transferred into a vacuum tube furnace and dried for 12 h by passing argon gas. The temperature of the vacuum tube furnace was set at 120° C., the heating rate was 7° C. / min, and the argon flow rate was 0.5 L / min. The product was ground and passed through a 40-mesh screen to obtain 16.5972 g of wheat straw sulfonated adsorbent.

[0093] Take high acid (C(H + )=1.995), 20mL of multi-element trace gold solution, 0.0400g of wheat straw sulfonated adsorbent, at room temperature, oscillate in a constant temperature oscillator for 24h, with a rotation speed of 250r / min. After analysis and calculation, the adsorbent prepared in this embodiment has an Au adsorption rate of 40.0%, an As adsorption rate of 0.2%, a Bi adsorption rate of 4.9%, a Cu adsorption rate of 3.7%, a Pb adsorption rate of 2.2%, and a Te adsorption rate of 4.0%. The pH value of the solution after adsorption is measured by a pH meter to be 1.84. The specific results are shown in Table 5.

[0094] Table 5 Comparative Example 2 Adsorption results of adsorbent

[0095]

[0096]

[0097] It can be seen from Table 5 that in Comparative Example 2, N235 modification was not used, and the adsorption rate of Au by the prepared adsorbent was relatively low.

[0098] Comparative Example 3

[0099] Preparation method of adsorbent: (1) Sulfonation: Weigh 20.0000 g corn stalks and add them to a beaker. Then, measure 50 mL of distilled water and add it to the beaker. Measure 50 mL of concentrated sulfuric acid (concentration is 18 mol / L) and slowly add it to the beaker. Stir with a glass rod to ensure that the corn stalks are in full contact with the concentrated sulfuric acid. After the corn stalks are completely carbonized, place them in a vacuum dryer with a vacuum degree of 1×10 -1 MPa, sealed and allowed to stand for three hours to obtain sulfonated corn stover;

[0100] (2) Neutralization: 150 mL of deionized water was added to the sulfonated corn stover obtained in step (1), and the pH was adjusted to 7.00 using a 4 mol / L NaOH solution, followed by filtering. The filtered solid was first washed three times with 10 mL of a 40% by volume ethanol solution, and then washed three times with 10 mL of deionized water. The solid was then separated into a solid and a liquid in a centrifuge to obtain a neutralized product. The rotation speed of the centrifuge was 3000 rpm, and the centrifugation time was 10 min.

[0101] (3) Drying: The neutralized product obtained in step (2) was transferred into a vacuum tube furnace and dried for 12 h by passing argon gas. The temperature of the vacuum tube furnace was set to 120° C., the heating rate was 7° C. / min, and the argon flow rate was 0.5 L / min. The product was ground and passed through a 40-mesh screen to obtain 17.6830 g of corn straw sulfonated adsorbent.

[0102] Take high acid (C(H + )=1.995), 20mL of multi-element trace gold solution, 0.0400g of corn straw sulfonated adsorbent, at room temperature, oscillate in a constant temperature oscillator for 24h, with a rotation speed of 250r / min. After analysis and calculation, the adsorbent prepared in this embodiment has an Au adsorption rate of 40.7%, an As adsorption rate of 0.2%, a Bi adsorption rate of 2.7%, a Cu adsorption rate of 4.4%, a Pb adsorption rate of 6.2%, and a Te adsorption rate of 6.1%. The pH value of the solution after adsorption is measured by a pH meter to be 1.84. The specific results are shown in Table 6.

[0103] Table 6 Comparative Example 3 adsorption results of adsorbent

[0104]

[0105] It can be seen from Table 6 that in Comparative Example 3, N235 modification was not used, and the adsorption rate of Au by the prepared adsorbent was relatively low.

[0106] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a green targeted gold adsorbent suitable for trace gold in a high-acid polybasic solution, characterized in that: The following steps are involved: (1) adding water and concentrated sulfuric acid to the biomass to perform sulfonation treatment to obtain sulfonated biomass; (2) mixing the sulfonated biomass with N235 to carry out a hydrothermal reaction, and performing solid-liquid separation after the reaction is completed, and the obtained solid is the hydrothermal synthesis product; (3) neutralizing the hydrothermal synthesis product with a sodium hydroxide solution, filtering, washing the filtered solid with an ethanol solution and water, respectively, and centrifuging to obtain a neutralized product; (4) Drying the neutralized product under an inert atmosphere, grinding and screening to obtain the green targeted gold adsorbent suitable for trace gold in high-acid polybasic solution.

2. The method for preparing a green targeted gold adsorbent suitable for trace gold in a high-acid polybasic solution according to claim 1, characterized in that: In step (1), the biomass includes corn cobs, wheat straw or corn straw.

3. The method for preparing a green targeted gold adsorbent suitable for trace gold in a high-acid polybasic solution according to claim 1, characterized in that: In step (1), the mass volume ratio of the biomass, water and concentrated sulfuric acid is 20 g: 50 mL: 50 mL.

4. The method for preparing a green targeted gold adsorbent suitable for trace gold in a high-acid polybasic solution according to claim 1, characterized in that: In step (1), the sulfonation process includes: Water and concentrated sulfuric acid are added to the biomass in sequence, and the mixture is stirred continuously. After the biomass is completely carbon black, the biomass is vacuum dried, sealed and allowed to stand for three hours to obtain the sulfonated biomass.

5. The method for preparing a green targeted gold adsorbent suitable for trace gold in a high-acid polybasic solution according to claim 1, characterized in that: In step (2), the mass volume ratio of the sulfonated biomass to N235 is (0.5-2) g:1 mL.

6. The method for preparing a green targeted gold adsorbent suitable for trace gold in a high-acid polybasic solution according to claim 1, characterized in that: In step (3), the step of obtaining the neutralized product is: Water is added to the hydrothermal synthesis product, and the pH is adjusted to 7.00 with a sodium hydroxide solution, filtered, and the filtered solid is first washed three times with a 40% by volume ethanol solution, and then washed three times with deionized water, centrifuged, and a neutralized product is obtained.

7. The method for preparing a green targeted gold adsorbent suitable for trace gold in a high-acid polybasic solution according to claim 1, characterized in that: In step (4), the inert atmosphere is argon, the drying temperature is 120° C., the heating rate during the drying process is 7° C. / min, and the argon flow rate is 0.5 L / min.

8. A green targeted gold adsorbent suitable for trace gold in high-acid polybasic solution, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the green targeted gold adsorbent according to claim 8 in targeted adsorption of gold in a high-acid polybasic solution.